Analisis Kritik Marxisme dalam Cerpen Semilyar ikan Memakan anjing-anjing dan Pabrik Skripsi Pada Antologi Cerpen Kompas 2014 - Annisa Aprilia Haque; Lia Camellia; Nur’afiah Fauziah; Seli Mauludani (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to reveal how short stories can represent social criticism related to class inequality in society, and aims to describe the forms of class conflict, social oppression, and class consciousness depicted in two short stories entitled "Thesis Factory" and "A Billion Fish Eat Dogs" in the 2014 Kompas Short Story Anthology using Karl Marx's Marxist literary criticism theory. Both short stories present the social reality of modern society which is full of capitalist practices, commercialization, and power inequality between the bourgeoisie and the proletariat. This study uses a descriptive qualitative method with data collection techniques in the form of literature study and text analysis. Literature study was conducted by collecting various references that are relevant/in accordance with Marxist literary criticism theory, while data analysis techniques include in-depth reading of story elements, interpretation of social symbols, and identification of class structures that appear in the narrative. The results of the study show that the short story "Thesis Factory" highlights the phenomenon of commercialization of education which gives rise to alienation and intellectual prostitution among academics. Meanwhile, the short story "A Billion Fish Eat Dogs" depicts ecological and social oppression as a metaphor for capitalist exploitation by the ruling class against the oppressed. Both works demonstrate critical awareness of unjust social systems and call for resistance to capitalism. Thus, this study confirms that literary works function not only as aesthetic media but also as a means of social critique of structural inequalities in society. Keywords: Marxism; literary criticism; class conflict.